2021
DOI: 10.1111/jopr.13430
|View full text |Cite
|
Sign up to set email alerts
|

The Flexural Strength and Flexural Modulus of Stereolithography Additively Manufactured Zirconia with Different Porosities

Abstract: Purpose: Additive manufacturing (AM) technologies are capable of fabricating complex geometries with different porosities. However, the effect of such porosities on mechanical properties of stereolithography (SLA) AM zirconia with different porosities is unclear. The purpose of this in vitro study was to investigate the mechanical properties namely flexural strength, and flexural modulus of AM zirconia with different porosities. Materials and Methods: A bar (25 × 4 × 3 mm) for flexural strength test (ISO stand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 56 publications
3
28
2
Order By: Relevance
“…However, 3 studies reported higher flexural strength for AM ceramics, which was contrary to the meta‐analysis in this systematic review, with 2 of these studies using zirconia, 60,43 and one using alumina 42 . For the studies on zirconia, this could be attributed to the use of high translucency and low strength SM zirconia as a control in one study 60 . The other study reported far higher flexural strength than what is reported in similar literature.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…However, 3 studies reported higher flexural strength for AM ceramics, which was contrary to the meta‐analysis in this systematic review, with 2 of these studies using zirconia, 60,43 and one using alumina 42 . For the studies on zirconia, this could be attributed to the use of high translucency and low strength SM zirconia as a control in one study 60 . The other study reported far higher flexural strength than what is reported in similar literature.…”
Section: Discussioncontrasting
confidence: 99%
“…A total of 16 in vitro studies were included in the qualitative analysis 35,42‐45,47,58‐67 43,45,58–61,66,67 alumina (3 studies)], 35,42,62 hardness [zirconia (2 studies), 58,64 alumina (2 studies)], 35,62 fracture toughness [zirconia (1 study), 64 alumina (2 studies)], 35,62 morphology [zirconia (2 studies), 58,64 alumina (1 study)], 62 roughness [zirconia, (2 studies)], 58,64 Weibull distribution [zirconia (2 studies), 59,61 alumina (2 studies)], 62,42 density [zirconia (2 studies)], 61,64 sintering shrinkage [zirconia (2 studies)], 61,42 structure [zirconia (4 studies)], 44,61,64,67 fracture resistance [zirconia (2 studies)], 47,65 load bearing capacity [zirconia (1 study)], 63 wettability [zirconia (1 study)], 64 biocompatibility [zirconia (1 study)], 64 elastic modulus [zirconia (1 study)], 44 and chemical composition [zirconia (2 studies)] 61,43 (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations